Functional characterization of a mouse model for central post-stroke pain - Gritsch, Simon; Bali, Kiran Kumar; Kuner, Rohini; Vardeh, Daniel (Molecular pain, 2016)
Background - Stroke patients often suffer from a central neuropathic pain syndrome called central post-stroke pain. This syndrome is characterized by evoked pain hypersensitivity as well as spontaneous, on-going pain in the body area affected by the stroke. Clinical evidence strongly suggests a dysfunction in central pain pathways as an important pathophysiological factor in the development of central post-stroke pain, but the exact underlying mechanisms remain poorly understood. To elucidate the underlying pathophysiology of central post-stroke pain, we generated a mouse model that is based on a unilateral stereotactic lesion of the thalamic ventral posterolateral nucleus, which typically causes central post-stroke pain in humans. - - Results - Behavioral analysis showed that the sensory changes in our model are comparable to the sensory abnormalities observed in patients suffering from central post-stroke pain. Surprisingly, pharmacological inhibition of spinal and peripheral key components of the pain system had no effect on the induction or maintenance of the evoked hypersensitivity observed in our model. In contrast, microinjection of lidocaine into the thalamic lesion completely reversed injury-induced hypersensitivity. - - Conclusions - These results suggest that the evoked hypersensitivity observed in central post-stroke pain is causally linked to on-going neuronal activity in the lateral thalamus.
Gesehen am 07.08.2020